Densities of maximal embedding dimension numerical semigroups - Iglésias, Laura (2018)
We define the density of a numerical semigroup and study the densities of all the maximal embedding dimension numerical semigroups with a fixed Frobenius number, as well as the possible Frobenius number for a fixed density. We also prove that for a given possible density, in the sense of Wilf's conjecture, one can find a maximal embedding dimension numerical semigroup with that density.